Morpho-anatomical characterization and DNA barcoding analysis of Pluchea indica (L.) Less. (Biodiversitas Journal of Biological Diversity, 2022)
Abstract. Wahyuni DK, Mukarromah SR, Rakhmad P, Ilham M, Rakashiwi GA, Indriati DT, Yoku BF, Purnobasuki H, Junairiah, Prasongsuk S. 2022. Morpho-anatomical characterizationand DNA barcoding analysisof Pluchea indica (L.) Less.. Biodiversitas 23: 4272-4282. Pluchea indica (L.) Less. is a member of the Asteraceae family and is popular as a medicinal plant. It is very important to authenticate plants using various markers to confirm the labeling of plants and to reveal the bioactive compounds for pharmaceutical research. This study aims to characterize the morpho-anatomical and DNA barcoding aspects of P. indica. Three samples obtained from Taman Husada Graha Famili, Surabaya, Indonesia were used in this study. Morphological studies were carried out descriptively, while the paraffin method was used for anatomical observations. DNA barcoding analysis was performed by amplifying and aligning the rbcLand matKgenes. Morphologically, P. indicahas organs like Asteraceae plants in general, with specific characteristics in leaves and flowers. P. indica has an anatomical organ similar to that of Asteraceae plants globally, only that there are specific histological features on its leaves, including anomocytic stomata, glandular cells, and multicellular glandular trichomes. Alignment and reconstruction of the phylogenetic tree showed that the sample plants were closely related to P. indica in the GenBank database. Based on morpho-anatomical characters and DNA barcodes, the plant under study was confirmed as P. indica L. (Less).